Wolf Use of Summer Territory in Northeastern Minnesota - Demma, Dominic J.; Mech, L. David (DigitalCommons@University of Nebraska - Lincoln, 2009)
Movements of wolves (Canis lupus) during summer 2003 and 2004 in the Superior National Forest were based around homesites but included extensive use of territories. Away from homesites, wolves used different areas daily, exhibiting rotational use. Mean daily range overlap was 22% (SE = 0.02) and that of breeding wolves was significantly greater than for nonbreeders (x = 25% and 16%, respectively). Rotational use may improve hunting success. Managers seeking to remove entire packs must maintain control long enough to ensure that all pack members are targeted.